Distributed feedback laser action from polymeric waveguides doped with oligo phenylene vinylene model compounds - BLAU, WERNER (My University, 2000)
We report lasing studies of poly~styrene ! waveguides doped with amino- and cyano-substituted oligo phenylene vinylene ~ distyryl benzene ! model compounds under picosecond excitation. Optical feedback is provided by distributed Bragg gratings formed in the film by interference patterns in the pump beam. We demonstrate broad tunability of laser emission in these materials and simultaneous lasing at two wavelengths separated by 23 nm. Tuning ranges of the model compounds are compared with previous experiments.
PUBLISHED
Keywords: oligo phenylene vinylene; oligo phenylene vinylene